Analysis of Variables Affecting Employee Performance - Romadhan, Ardian Nur; Sarwono, Aris Eddy; Handayani, Asih (Prosiding University Research Colloquium, 2022)
This systematic literature review is used to analyze the variables that affect employee performance and to find out what analytical methods and objects along with the number of research samples used by previous researchers are gaps for future research. The research method uses a systematic literature review. The research data was obtained through a search for publications in the range of 2018 to 2021 with the keywords of employee performance being captured based on a quantitative approach. The number of publications analyzed were 20 journals/articles/proceedings. Data were analyzed qualitatively. From this literature review, it can be seen that various predictor variables have been shown to affect employee performance with various analytical methods, objects and the number of samples. For future research development, apart from testing the direct effect, it is also possible to test the indirect effect, either testing a single mediator model or multiple mediator models using path analysis or factor analysis (structural equation modeling).